A meta-analysis of microRNA networks regulated by melatonin in cancer: Portrait of potential candidates for breast cancer treatment - Chuffa, Luiz Gustavo de Almeida [UNESP]; Carvalho, Robson Francisco [UNESP]; Justulin, Luis Antônio [UNESP]; Cury, Sarah Santiloni [UNESP]; Seiva, Fábio Rodrigues Ferreira; Jardim-Perassi, Bruna Victorasso; Zuccari, Debora Aparecida Pires de Campos; Reiter, Russel J. (Wiley, 2020)
Melatonin is a ubiquitous molecule with a broad spectrum of functions including widespread anti-cancer activities. Identifying how melatonin intervenes in complex molecular signaling at the gene level is essential to guide proper therapies. Using meta-analysis approach, herein we examined the role of melatonin in regulating the expression of 46 microRNAs (miRNAs) and their target genes in breast, oral, gastric, colorectal, and prostate cancers, and glioblastoma. The deregulated miRNA-associated target genes revealed their involvement in the regulation of cellular proliferation, differentiation, apoptosis, senescence, and autophagy. Melatonin changes the expression of miRNA-associated genes in breast, gastric, and oral cancers. These genes are associated with cellular senescence, the hedgehog signaling pathway, cell proliferation, p53 signaling, and the hippo signaling pathway. Conversely, colorectal and prostate cancers as well as glioblastoma and oral carcinoma present a clear pattern of less pronounced changes in the expression of miRNA-associated genes. Most notably, colorectal cancer displayed a unique molecular change in response to melatonin. Considering breast cancer network complexity, we compared the genes found during the meta-analysis with RNA-Seq data from breast cancer-bearing mice treated with melatonin. Mechanistically, melatonin upregulated genes associated with immune responses and apoptotic processes, whereas it downregulated genes involved in cellular aggressiveness/metastasis (eg, mitosis, telomerase activity, and angiogenesis). We further characterized the expression profile of our gene subsets with human breast cancer and found eight upregulated genes and 16 downregulated genes that were appositively correlated with melatonin. Our results pose a multi-dimension network of tumor-associated genes regulated by miRNAs potentially targeted by melatonin.
Keywords: cancer; melatonin; microRNA; miRNA regulatory network; target genes